Analysis of Crude Palm Oil Processing toward Environmental Impact at PT. Bersama Oesaha Saragih Sejahtera - Asmina Herawaty Sinaga; Hery Andi Sitompul; Alimin Purba (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to identify internal (Opportunities and Threats) in palm oil development strategies, formulate alternative development strategies in palm oil processing. The research result show that the strength factors of the development strategy in palm oil processing in the research area are due to the quality of CPO and availability of palm fruit, while the weakness factors are due to the quality of human resources, company conditions, environmental strategies in palm oil processing in the research area due todemand for CPO and information technology, while the threat factors are competition for CPO, price fluctuations. With the weighting results of the SWOT analysis results with IFAS and EFAS, SO = 3,93, ST = 3.47, WO = 2.66, WT = 2.25. And the results of the QSPM strategy 1 matrix improve the quality of CPO to meet the increasing demand for market share and utilize the availability of palm fruit and infrastructure to increase production with the highest Total Attractive Score (TAS) value, namely 7.310 among other alternative TAS values, strategy 2 with a Total Attractive Score (TAS value of 6,240 and strategy 4 with a Total Attractive Score (TAS) value of 4,480.